Maritime Academy Accepts Applications - Star News (Star News)
Applications for admittance to the California State Maritime Academy next fall are now bemg accepted, Capt. Claude Mayo, superintendent of the Academy announced yesterday. The academy, located at Morro Cove, Vallejo, trains young Californians for officer positions in the United States Merchant Marine.